Photovoltaic panel surface dust deposition resistant coating and preparation method thereof

By spraying composite coatings composed of FEP and nano-indium tin oxide on the surface of the photovoltaic panel, the problem of ash pollution in the surface area of ​​the photovoltaic panel is solved, and the efficient anti-ash effect in sand and dust environment is achieved, and the performance of the photovoltaic system is improved. and maintainability.

CN119505611APending Publication Date: 2025-02-25NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411434811.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The ash accumulation on the surface of photovoltaic panels is seriously polluted, affecting the performance and efficiency of solar cells. The existing high-performance anti-ash coating materials are relatively scarce, especially in sand and dust environments, which are difficult to effectively solve.

Method used

Using photovoltaic panel surface anti-grain coating made of FEP, nano-indium tin oxide, surfactant and FC-4, the FEP-nano-indium tin oxide composite coating is formed by spraying, which has long-lasting dust resistance and easy cleaning characteristics. .

Benefits of technology

The composite coating formed by this coating has excellent anti-fouling ability, which can effectively reduce ash pollution in a sand-dust environment, improve the energy output and maintenance of the photovoltaic system, and reduce operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505611A_ABST
    Figure CN119505611A_ABST
Patent Text Reader

Abstract

The invention discloses a photovoltaic panel surface dust deposition resistant coating and a preparation method thereof, and belongs to the technical field of new materials. The dust deposition resistant coating for the surface of the photovoltaic panel is prepared from the following raw materials in percentage by mass: 1 to 8 percent of FEP, 3.5 to 7.5 percent of nano indium tin oxide, 0.08 to 0.8 percent of a surfactant, 0.02 to 0.5 percent of FC-4 and the balance of a solvent. When the anti-dust deposition coating is applied (sprayed) to the surface of a photovoltaic panel, an FEP-nano indium tin oxide composite coating can be formed, and the coating can show lasting anti-pollution ability and is easy to clean. When the photovoltaic cell coated with the special coating is used in a dusty environment, compared with a photovoltaic cell without a coating or only with a traditional antireflection coating, the photovoltaic cell coated with the special coating has unique advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a photovoltaic panel surface anti-dust coating and a preparation method thereof. Background Art

[0002] In the current clean energy field, photovoltaic technology has been widely used as an important source of renewable energy. However, the pollution problem on the surface of photovoltaic panels has attracted increasing attention, among which dust pollution is particularly serious, which directly affects the performance and efficiency of solar cells. The dust accumulation on the surface of photovoltaic panels is mainly caused by pollutants such as suspended particles, fine dust, and dust in the air. These pollutants accumulate on the surface of photovoltaic panels, blocking sunlight and significantly reducing the power generation efficiency of the battery.

[0003] Dust pollution not only reduces the energy output of photovoltaic systems, but also increases the frequency of cleaning and maintenance, thereby increasing the operating costs of photovoltaic systems. Therefore, the development of an efficient anti-dust pollution coating on the surface of photovoltaic panels has important scientific research and engineering application significance. This coating can effectively reduce the adverse effects of dust pollution on the performance of photovoltaic panels, improve the energy output of the system, and reduce maintenance costs.

[0004] The development of anti-dust coatings on photovoltaic panels also has a positive impact on environmental protection and sustainable development. By reducing the use of cleaning chemicals, environmental pollution in the clean energy production process can be reduced, thereby promoting the sustainable development of the clean energy industry. This technology can not only improve the performance and maintainability of photovoltaic systems, but also have a positive effect on the development of renewable energy and environmental protection, and contribute to addressing climate change and achieving carbon reduction targets.

[0005] Therefore, the anti-dust coating on the surface of photovoltaic panels has broad application prospects and far-reaching social significance. However, high-performance anti-dust coating materials are relatively scarce in the market, especially for harsh dusty environments. It is urgent to develop photovoltaic surface anti-dust coating materials suitable for different environments. Summary of the invention

[0006] The purpose of the present invention is to provide a photovoltaic panel surface anti-dust coating and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The photovoltaic panel surface anti-dust coating provided by the present invention can form a durable, dust-resistant and easy-to-clean coating on the surface of the photovoltaic panel.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention is a photovoltaic panel surface anti-dust coating, which comprises, by mass percentage, 1-8% FEP (perfluoroethylene propylene copolymer), 3.5-7.5% nano indium tin oxide, 0.08-0.8% surfactant, 0.02-0.5% FC-4 (perfluorobutylene sulfonyl fluoride) and the remainder solvent.

[0009] Furthermore, the surfactant is sodium dodecyl sulfate; and the FEP is specifically a FEP emulsion with a solid content of 60 wt%.

[0010] Using sodium dodecyl sulfate as a surfactant can disperse particles and droplets in the liquid to prevent them from agglomerating or settling, which helps to stabilize the suspended liquid and prevent the formation of precipitation. At the same time, sodium dodecyl sulfate has good detergency.

[0011] FEP is a perfluoroethylene-propylene copolymer, abbreviated as FEP, which is a type of perfluoroolefin. It has very high chemical inertness and is not corroded by acids, alkalis, solvents and most chemicals. Secondly, FEP material also has good light transmittance. Using it as the main component of anti-dust coating on the surface of photovoltaic panels does not affect the light transmittance.

[0012] Furthermore, the solvent is water and / or ethanol.

[0013] Furthermore, the particle size of the nano-indium tin oxide is 30-60 nm; the nano-indium tin oxide is prepared by a sol-gel method.

[0014] Furthermore, the preparation steps of the nano indium tin oxide include: mixing an organic solvent, indium nitrate, indium tetrachloride and water to obtain a mixed solution; adding dilute hydrochloric acid to the mixed solution until the pH of the mixed solution system is 5.8-6.3, stirring the reaction for 10-30 minutes, and standing for 2-4 hours (to allow the sol to fully age) to obtain a sol; drying and calcining the sol to obtain the nano indium tin oxide.

[0015] Furthermore, the organic solvent is an ethanol solution; the usage ratio of the organic solvent, indium nitrate, indium tetrachloride and water is 100-200mL:30-50g:20-40mL:300-600mL.

[0016] Furthermore, the specific operation of mixing the organic solvent, indium nitrate, indium tetrachloride and water to obtain a mixed solution is: adding indium nitrate and tin tetrachloride to the organic solvent respectively, then slowly adding water, and magnetically stirring for 30 minutes to avoid uneven gel formation caused by too fast reaction.

[0017] Furthermore, the concentration of the dilute hydrochloric acid is 30wt%; the dilute hydrochloric acid serves as a catalyst in the reaction system.

[0018] Furthermore, the drying temperature is 75-85° C. and the drying time is 2 hours.

[0019] Furthermore, the calcination temperature is 350-550° C. Calcination is to remove organic impurities and form crystalline nano-indium tin oxide.

[0020] Furthermore, the purity of the nano-indium tin oxide is 96.5-99.8%.

[0021] The second technical solution of the present invention: The preparation method of the above-mentioned anti-dust coating on the surface of the photovoltaic panel comprises the following steps: adding nano indium tin oxide, FEP, FC-4 and a surfactant to the solvent in sequence, mixing them evenly, and obtaining the anti-dust coating on the surface of the photovoltaic panel.

[0022] Furthermore, after each component is added, magnetic stirring is performed for 10-30 minutes, and then ultrasonic dispersion is performed for 30-60 minutes.

[0023] The third technical solution of the present invention: application of the above-mentioned anti-dust deposition paint on the surface of photovoltaic panels in the preparation of anti-dust deposition coating on the surface of photovoltaic panels.

[0024] Furthermore, the specific operation of preparing the anti-dust coating on the surface of the photovoltaic panel is: spraying the anti-dust coating on the surface of the photovoltaic panel, and drying to form the anti-dust coating; the thickness of the anti-dust coating is 50-100 μm.

[0025] When the anti-fouling coating of the present invention is applied (sprayed) to the surface of a photovoltaic panel, a FEP-nano indium tin oxide composite coating is formed, which exhibits a long-lasting anti-fouling ability and is easy to clean. Photovoltaic cells coated with this special coating have unique advantages over photovoltaic cells without coating or with only traditional anti-reflection coating when used in dusty environments.

[0026] The present invention discloses the following technical effects:

[0027] (1) The anti-dust coating for the photovoltaic panel surface provided by the present invention uses FEP and nano-indium tin oxide as main components. FEP is a new type of material with a higher density than the commonly used coating material PTFE, and has excellent chemical corrosion resistance. Its creep resistance and compression strength are both higher than PTFE. Secondly, the operating temperature of FEP is also higher than PTFE, and it has better thermal stability. More importantly, FEP has a very low surface energy, which makes the coating surface smooth and not easy to adhere to dust, dirt and other particles, which is conducive to reducing the adhesion of pollutants and making dust and dirt easier to be naturally removed by wind and rain. Moreover, the chemical corrosion resistance of FEP not only protects the surface of the photovoltaic panel from the invasion of chemical substances, but also helps to maintain the integrity and smoothness of the coating surface, thereby further reducing dust accumulation. Nano-indium tin oxide can effectively reduce the permeability of acidic substances and successfully protect photovoltaic glass from being corroded by acid rain and other acidic substances (such as bird droppings, worms, etc.). In addition, inorganic nano-indium tin oxide has high hardness and wear resistance, which prevents the formation of scratches on the surface of the photovoltaic panel. Moreover, due to its nanometer-scale particle size, indium tin oxide can form a dense structure in the coating, which increases the smoothness and consistency of the coating and helps prevent the deposition of tiny particles. The combination of FEP and indium tin oxide improves the overall smoothness and chemical stability of the coating. FEP provides a basic low-adhesion surface, and indium tin oxide further enhances this property, reducing the deposition and accumulation of dirt through its structure. Moreover, the addition of sodium dodecyl sulfate, which has good decontamination ability, not only improves the stability of the coating, but also further improves the anti-fouling ability of the coating. The addition of FC-4 plays a role in further improving the performance of the coating. FC-4 is a surfactant that can significantly reduce the surface tension of the coating, so that the coating can be more evenly distributed on the surface of the photovoltaic panel during the coating process, which can not only enhance the smoothness of the coating, but also further reduce the adhesion of dust and dirt. The above components work together to make the coating of the present invention have excellent anti-dust deposition ability. In addition, the high hardness and wear resistance of indium tin oxide ensure the long-term use performance of the coating, while the weather resistance of FEP ensures the stability of the coating under various environmental conditions. These characteristics jointly extend the effective life and function of the coating.

[0028] (2) The method for preparing the anti-dust coating on the surface of photovoltaic panels provided by the present invention has simple steps and mild reaction conditions, and is suitable for large-scale industrial production.

[0029] (3) The anti-dust coating on the photovoltaic panel surface provided by the present invention can not only improve the performance and maintainability of the photovoltaic system, but also have a positive impact on the development of renewable energy and environmental protection, and contribute to addressing climate change and carbon emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a SEM image of the FEP-nano indium tin oxide composite coating formed by spraying the coating of Example 1. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] In the specific embodiments of the present invention, all steps without particular limitation on the operating temperature are carried out at room temperature, which specifically refers to 20-30°C.

[0038] Example 1

[0039] A preparation method of anti-dust coating on the surface of photovoltaic panels, comprising the following steps:

[0040] (1) Take 30 g of indium nitrate (In(NO 3 ) 3 ) and 40mL of tin tetrachloride (SnCl 4 ) is slowly added into 100mL of 95vol% ethanol solution, and then 300mL of deionized water is slowly added, and magnetic stirring is carried out for 30min to obtain a mixed solution; 30wt% dilute hydrochloric acid is added to the mixed solution until the pH value of the mixed solution system reaches 5.8, and after stirring for 10min, it is allowed to stand for 2h to allow the sol to fully age; the solution after standing is placed in a drying oven for drying, the drying temperature is set to 75°C, and the drying time is 2h; the dried gel is taken out and calcined at a temperature set to 350°C until the material is completely crystalline to obtain nano indium tin oxide particles (after testing, the purity is 97.8%, and the average particle size of nano indium tin oxide is 45nm).

[0041] (2) Add 30 g of the nano indium tin oxide particles obtained in step (1) to 500 mL of deionized water, stir magnetically for 30 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 1 h; then take 20 g of 60 wt% solid content FEP emulsion and slowly add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; then take 1 g of FC-4 active agent and add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; finally, add 2 g of sodium dodecyl sulfate, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min to form a final spray coating.

[0042] Example 2

[0043] A preparation method of anti-dust coating on the surface of photovoltaic panels, comprising the following steps:

[0044] (1) Take 50g of indium nitrate (In(NO 3 ) 3 ) and 20mL of tin tetrachloride (SnCl 4) was slowly added to 120 mL of 95 vol% ethanol solution, and then 300 mL of deionized water was slowly added, and magnetic stirring was performed for 30 min to obtain a mixed solution; 30 wt% dilute hydrochloric acid was added to the mixed solution until the pH value of the mixed solution system reached 6.1, and the solution was stirred for 10 min and then allowed to stand for 2 h to allow the sol to fully age; the solution after standing was placed in a drying oven for drying, the drying temperature was set to 80°C, and the drying time was 2 h; the dried gel was taken out and calcined at a temperature set to 320°C until the material was completely crystalline to obtain nano indium tin oxide particles (after testing, the purity was 97.1%, and the average particle size of nano indium tin oxide was 58.2 nm).

[0045] (2) Add 20 g of the nano indium tin oxide particles obtained in step (1) to 500 mL of deionized water, stir magnetically for 30 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 1 h; then take 30 g of 60 wt% solid content FEP emulsion and slowly add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; then take 1.5 g of FC-4 active agent and add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; finally, add 1.5 g of sodium dodecyl sulfate, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min to form a final spray coating.

[0046] Example 3

[0047] A preparation method of anti-dust coating on the surface of photovoltaic panels, comprising the following steps:

[0048] (1) Take 40 g of indium nitrate (In(NO 3 ) 3 ) and 30mL of tin tetrachloride (SnCl 4 ) is slowly added into 140mL of 95vol% ethanol solution, and then 400mL of deionized water is slowly added, and magnetic stirring is carried out for 30min to obtain a mixed solution; 30wt% dilute hydrochloric acid is added to the mixed solution until the pH value of the mixed solution system reaches 5.9, and after stirring for 10min, it is allowed to stand for 2h to allow the sol to fully age; the solution after standing is placed in a drying oven for drying, the drying temperature is set to 85°C, and the drying time is 2h; the dried gel is taken out and calcined at a temperature set to 400°C until the material is completely crystalline to obtain nano indium tin oxide particles (after testing, the purity is 96.9%, and the average particle size of nano indium tin oxide is 43nm).

[0049] (2) Add 25 g of the nano indium tin oxide particles obtained in step (1) to 500 mL of deionized water, stir magnetically for 30 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 1 h; then take 45 g of 60 wt% solid content FEP emulsion and slowly add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; then take 2 g of FC-4 active agent and add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; finally, add 1 g of sodium dodecyl sulfate, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min to form a final spray coating.

[0050] Example 4

[0051] A preparation method of anti-dust coating on the surface of photovoltaic panels, comprising the following steps:

[0052] (1) Take 45g of indium nitrate (In(NO 3 ) 3 ) and 35 mL of tin tetrachloride (SnCl 4 ) is slowly added into 80mL of 95vol% ethanol solution, and then 500mL of deionized water is slowly added, and magnetic stirring is carried out for 30min to obtain a mixed solution; 30wt% dilute hydrochloric acid is added to the mixed solution until the pH value of the mixed solution system reaches 6.3, and after stirring for 10min, it is allowed to stand for 2h to allow the sol to fully age; the solution after standing is placed in a drying oven for drying, the drying temperature is set to 82°C, and the drying time is 2h; the dried gel is taken out and calcined at a temperature set to 500°C until the material is completely crystalline to obtain nano indium tin oxide particles (after testing, the purity is 98.7%, and the average particle size of nano indium tin oxide is 55.6nm).

[0053] (2) Add 35 g of the nano indium tin oxide particles obtained in step (1) to 500 mL of deionized water, stir magnetically for 30 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 1 h; then take 35 g of 60 wt% solid content FEP emulsion and slowly add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; then take 2.5 g of FC-4 active agent and add it to the above solution, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min; finally, add 0.5 g of sodium dodecyl sulfate, stir magnetically for 10 min, and then put it into an ultrasonic water tank for ultrasonic dispersion for 30 min to form a final spray coating.

[0054] Comparative Example 1

[0055] Same as Example 1, except that in step (2), 20 g of 60 wt % solid content FEP emulsion is replaced by 20 g of 60 wt % solid content PTFE emulsion.

[0056] Comparative Example 2

[0057] The same as Example 1, except that in step (2), an equal mass of perfluorooctanoic acid (PFOA) is used instead of FC-4.

[0058] Comparative Example 3

[0059] The same as Example 1, except that in step (2), an equal amount of sodium dodecylbenzene sulfonate is used instead of sodium dodecyl sulfate.

[0060] Effect verification

[0061] The coatings prepared in Examples 1-4 were sprayed on the surface of photovoltaic panels to form anti-dust coatings, and the anti-dust coatings were subjected to water contact angle tests and dust accumulation tests. The specific steps of the dust accumulation test are as follows:

[0062] ①Sample preparation:

[0063] Ensure that the surface of the photovoltaic panel sample is clean and dry. Use a spray device to evenly spray the coatings prepared in Examples 1-4 and Comparative Examples 1-2 on the photovoltaic panels to ensure uniform coating coverage. The photovoltaic panels without coating are used as the control group. Each group is set up with 3 repetitions, and the results are averaged. The coated samples and the uncoated samples are placed in a constant temperature and humidity laboratory environment for 24 hours to ensure that the coating is fully cured. The average thickness of the cured coating is 50 μm.

[0064] ② Ash scattering simulation:

[0065] Use a dust spraying device to evenly sprinkle the same amount of simulated dust on the photovoltaic panel sample. Ensure that the dust is evenly covered to simulate natural dust accumulation conditions. Use a hair dryer at a low wind speed to blow the dust so that it settles evenly.

[0066] ③Settling time:

[0067] The dust was allowed to sit on the surface of the PV panels for 24 hours to simulate the dust accumulation process.

[0068] ④Weigh the dust accumulation weight:

[0069] The dust weight on the surface of the coated and uncoated photovoltaic panels was weighed again using a balance.

[0070] The test results are shown in Table 1.

[0071] Table 1

[0072]

[0073] The SEM image of the FEP-nano indium tin oxide composite coating formed by spraying the coating of Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the average particle size of the FEP-nano indium tin oxide composite coating is about 45nm in microstructure, and the particles are evenly distributed in the FEP matrix without obvious agglomeration, with excellent uniformity and bonding strength. The surface of the composite coating looks relatively smooth, and the gaps between the particles are well filled. The smooth surface can reduce optical scattering and improve the light transmittance of the coating.

[0074] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A photovoltaic panel surface anti-dust coating, characterized in that: Calculated by mass percentage, the raw materials include: 1-8% FEP, 3.5-7.5% nano indium tin oxide, 0.08-0.8% surfactant, 0.02-0.5% FC-4 and the balance solvent.

2. The anti-dust coating for photovoltaic panel surface according to claim 1, characterized in that: The surfactant is sodium dodecyl sulfate; the FEP is specifically a FEP emulsion with a solid content of 60 wt%.

3. The anti-dust coating for photovoltaic panel surface according to claim 1, characterized in that: The solvent is deionized water and / or ethanol.

4. The anti-dust coating for photovoltaic panel surface according to claim 1, characterized in that: The particle size of the nano-indium tin oxide is 30-60nm; the nano-indium tin oxide is prepared by a sol-gel method.

5. The anti-dust coating for photovoltaic panel surface as claimed in claim 4, characterized in that: The preparation steps of the nano indium tin oxide include: mixing an organic solvent, indium nitrate, indium tetrachloride and water to obtain a mixed solution; adding dilute hydrochloric acid to the mixed solution until the pH of the mixed solution system is 5.8-6.3, stirring the reaction for 10-30 minutes, and standing for 2-4 hours to obtain a sol; and drying and calcining the sol to obtain the nano indium tin oxide.

6. The anti-dust coating for photovoltaic panel surface as claimed in claim 5, characterized in that: The organic solvent is an ethanol solution; the usage ratio of the organic solvent, indium nitrate, indium tetrachloride and water is 80-200mL:30-50g:20-40mL:300-600mL.

7. The anti-dust coating for photovoltaic panel surface as claimed in claim 5, characterized in that: The calcination temperature is 350-550°C.

8. The method for preparing the anti-dust coating on the surface of photovoltaic panels according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding nano indium tin oxide, FEP, FC-4 and a surfactant into a solvent in sequence, and mixing them evenly to obtain the anti-dust coating on the surface of the photovoltaic panel.

9. The preparation method according to claim 8, characterized in that: After adding each component, stir magnetically for 10-30 minutes, and then disperse ultrasonically for 30-60 minutes.

10. Use of the anti-dust coating for photovoltaic panel surfaces as claimed in any one of claims 1 to 7 in the preparation of anti-dust coating for photovoltaic panel surfaces.